Blue Carbon Stock Assessment of The Mangrove Swamp Forest Reserve in Baganga, Davao Oriental, Philippines - Renz Morales Lanaban; Yves Paul M. Montero; Hilario L. Jr. Wong; Marnie Grace I. Sonico (Applied Environmental Research, 2025)
Mangrove ecosystems are vital carbon sinks, yet they are threatened by anthropogenic pressures and natural disturbances, causing significant carbon stock losses. Given the limited data for Baganga, Davao Oriental, this study quantified the aboveground biomass (AGB) and blue carbon stock in the Lucod mangrove swamp forest reserve. We identified mangrove species, measured AGB and carbon content via allometric equations, and compared storage among species. The results indicated that the mangrove forest AGB was within typical ranges for tropical wet regions and the Asia-Pacific region, but its overall carbon content did not reach highly productive ecosystem levels. Nonparametric analysis revealed significant heterogeneity in both the overall mangrove AGB across sites and the AGB among species. Among the six identified species, Lumnitzera littorea was the dominant carbon contributor (65%), whereas Rhizophora apiculata contributed the least (2%). These findings underscore the need for site- and species-specific approaches in mangrove management and future research to understand AGB variations.